Survival and sustainability environmental concerns in the 21st century - International Conference on Environment: Survival and Sustainability (2007 Nicosia, Cyprus); Gokçekuş, Huseyin; Turker, Umut.; LaMoreaux, James W.; SpringerLink (Online service). (Berlin London Springer, 2010)
nternational Conference on Environment: Survival and Sustainability, held at the Near East University, Nicosia, Northern Cyprus 19-24 February 2007, dealt with environmental threats and proposed solutions at all scales. The 21 themes addressed by the conference fell into four broad categories; Threats to Survival and Sustainability; Technological Advances towards Survival and Sustainability; Activities and Tools for Social Change; Defining Goals for Sustainable Societies. Activities and tools that move the society towards greater sustainability were emphasized at the conference. These included environmental law and ethics, environmental knowledge, technology and information systems, media, environmental awareness, education and lifelong learning, the use of literature for environmental awareness, the green factor in politics, international relations and environmental organizations. The breadth of the issues addressed at the conference made clear the need for greatly increased interdisciplinary and international collaboration the survival and sustainability concept. The exchanges at the conference represent a step in this direction.
Electronic reproduction.
Keywords: Environmental responsibility -- Congresses; Sustainable development -- Congresses; Electronic books